2021
DOI: 10.1111/jhn.12966
|View full text |Cite
|
Sign up to set email alerts
|

Pecan‐enriched diets increase energy expenditure and fat oxidation in adults at‐risk for cardiovascular disease in a randomised, controlled trial

Abstract: Background: Research indicates that diets enriched with unsaturated fatty acids improve energy metabolism, although studies on tree nuts, which are a rich source of those fats, are limited. The present study aimed to examine the impact of daily pecan consumption for 8 weeks on energy metabolism in adults with hypercholesterolaemia or at higher risk for cardiovascular disease (CVD) (body mass index ≥ 28 kg m -2 ). Methods: For this randomised, controlled trial, 56 sedentary adults were randomised into one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We previously showed that a 7-d PUFA-rich diet (containing walnuts) improved fasting and postprandial peptide YY, a satiety hormone ( 28 ) . Furthermore, previous research involving 8–19 weeks of peanut or pecan consumption resulted in a 5–11 % increase in resting metabolic rate ( 16 , 29 , 30 ) . Finally, we know that not all the energy in some nuts is fully metabolised and absorbed ( 31 , 32 ) .…”
Section: Discussionmentioning
confidence: 91%
“…We previously showed that a 7-d PUFA-rich diet (containing walnuts) improved fasting and postprandial peptide YY, a satiety hormone ( 28 ) . Furthermore, previous research involving 8–19 weeks of peanut or pecan consumption resulted in a 5–11 % increase in resting metabolic rate ( 16 , 29 , 30 ) . Finally, we know that not all the energy in some nuts is fully metabolised and absorbed ( 31 , 32 ) .…”
Section: Discussionmentioning
confidence: 91%
“…Participants had 10 min to drink the meal after which 4 oz of water was used to rinse out the container, which was then also consumed. HF meal challenges are commonly provided as a liquid rather than solid meal, [37][38][39] likely due to their ability to be consumed quickly and easily, and have been shown to be comparable for measuring circulatory markers of lipid metabolism and metabolic function parameters in previous studies. 40,41 An SFA-rich meal challenge was used to observe how diets enriched with CSO and OO influence metabolic responses to an occasional unhealthy meal.…”
Section: Prediet Intervention Visit (V1)mentioning
confidence: 99%